Empower Jatisari: Pelatihan Digitalisasi Dan Kelengkapan Legalitas UMKM Desa Jatisari Guna Peningkatan Value Usaha Dan Ekonomi Masyarakat Lokal : (Empower Jatisari: Digitalization Training and Legal Completeness of Jatisari Village MSMEs to Increase Business Value and Local Community Economy) - Johan Octavian; Sa’diyah, Lailatus; Ulfa, Safinah Musfidah; Tariaranie, Rayie (Vivabio: Jurnal Pengabdian Multidisiplin, 2024)
Empower Jatisari is outlined to extend the esteem of nearby businesses and economy in Jatisari Town through digitalization, preparation and counseling on the completeness of MSME lawfulness. This community benefit points to survey the affect of digitalization preparing on participants' abilities and understanding and its impacts on MSME operations. The strategies utilized in community benefit include pre- and post-training overviews, as well as in-depth interviews. Key discoveries demonstrate that digitalization preparing altogether makes strides participants' computerized understanding and aptitudes, which emphatically impacts the utilize of innovation in their businesses. In expansion, counseling on the completeness of legitimateness makes a difference MSMEs meet legitimate necessities, progressing the lawfulness and validity of their businesses. In spite of the fact that there are a few challenges related to foundation and starting understanding of members, this program appears awesome potential to make strides the nearby economy. Suggestions for encourage advancement and progressing back are recommended. ABSTRAK Empower Jatisari yang dirancang untuk meningkatkan nilai usaha dan ekonomi lokal di Desa Jatisari melalui pelatihan digitalisasi dan penyuluhan mengenai kelengkapan legalitas UMKM. pengabdian masyarakat ini bertujuan untuk menilai dampak pelatihan digitalisasi terhadap keterampilan dan pemahaman peserta serta efeknya pada operasi UMKM. Metode yang dilakukan dalam pengabdian masyarakat melibatkan survei pre-dan post-pelatihan, serta wawancara mendalam. Temuan utama menunjukkan bahwa pelatihan digitalisasi secara signifikan meningkatkan pemahaman dan keterampilan digital peserta, yang mempengaruhi penggunaan teknologi dalam usaha mereka secara positif. Selain itu, penyuluhan tentang kelengkapan legalitas membantu UMKM dalam memenuhi persyaratan hukum, meningkatkan legalitas dan kredibilitas usaha mereka. Meskipun terdapat beberapa tantangan terkait infrastruktur dan pemahaman awal peserta, program ini menunjukkan potensi besar untuk meningkatkan ekonomi lokal. Rekomendasi untuk pengembangan lebih lanjut dan dukungan berkelanjutan disarankan.